Dinamika Epistemologi Yuridis Ekonomi Syariah di Indonesia Perspektif Transisi Hukum H.L.A. Hart - Mohamad Nur Yasin (Ulumuna, 2015)
The dynamic of the juridical epistemology of Islamic economy in Indonesia passed through four phases, i.e. sharī‘ah, fiqh, qānūn, and qad\ā’. The first two phases have normative doctrinal characteristics while the last two show positive legal formal characteristics. The transformation of Islamic economic law started at the level of normative moral doctrinal to the level of legal formal. It has a methodological spirit which is closely related to the theory of legal transition by H.L.A. Hart. According to Hart, the transition from moral to law involves two concepts. First, primary rules which define the moral values embraced by the people. Second, secondary rules which modify and dynamite the primary rules to be legal binding for all the people. In this case, state authority is required to execute the rules. In Hart’s perspective on the transition of law, sharī‘ah and fiqh are the rules of etiquette and obligation. Meanwhile, qānūn, and qad\ā’ are the rules of recognition, rules of change, and rules of adjudication. In the transition of law, there is an interconnection between law and Islamic economy sustainably, professionally, and proportionally. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1257